Transgene introgression into wild cotton populations generates long-term genetic and ecological effects in a center of origin - Valeria Vázquez-Barrios; Ian A.E. Butler; Patricia Rojas; Ana Wegier (Environmental Pollution, 2026)

Repeated barrier drown-out is required to facilitate long-distance migration of a potamodromous fish - Jason D. Thiem; Benjamin G. Fanson; David Ryan; Gavin L. Butler; David A. Crook; Doug J. Harding; Anthony Townsend; Ian J. Wooden; Ivor Stuart (Aquatic Sciences, 2025)
Migratory fish species are highly vulnerable to stream fragmentation. Potamodromous golden perch ( Macquaria ambigua ) inhabit the barrier-laden Murray–Darling Basin (MDB), Australia’s largest river system, and its lifecycle includes a requirement for uninterrupted stretches of flowing water habitat. Owing to these barriers, large-scale connectivity in many regions is limited to periods of high flow events that facilitate barrier drown-out. We undertook a 3-year (2021–2024) study using telemetry to quantify the movements of 150 adult golden perch from the Barwon–Darling River over a period that encompassed numerous high flow events and flooding. Approximately 75% of tagged golden perch undertook movements > 50 km, with > 90% of movements in an upstream direction, extending up to 1500 km and associated with increased river discharge. Tributary entries were detected on multiple occasions, with an apparent preference for specific tributaries. Ten fish migrated > 1000 km upstream across multiple flow events. The results of this study (1) highlight the importance of the Barwon–Darling River and tributaries as a key migration conduit for adult golden perch, (2) demonstrate that multiple flow events are required to achieve large-scale dispersal and (3) provide quantitative flow-movement relationships that can be used to support inter-regional management actions. These management actions might include barrier removal, the construction of fishways and protection of tributary–mainstem flow events.

Controls on shear band orientation in deforming porous rocks: Insights from improved microcrack segmentation method - Claudia Elijas-Parra; Alexis Cartwright-Taylor; Ian G. Main; Rebeca E. Ursu; Ian B. Butler; Florian Fusseis (Journal of Structural Geology, 2025)

Covalently linked phosphate monoesters on alpha-polyglucans reduce substrate affinity of branching enzymes - Victoria Butler; Hanan Shaaban; Lilya Nasanovsky; Jessica K.V. White; Owen Hebb; Lynne Jones; Megan Whiting; Neije Mukherjee-Roy; Alina P. Montalbano; Carmen Elena Machado Vides; Felix Nitschke; Ian J. Tetlow (Carbohydrate Polymers, 2025)

Are recommended dosages of copper-based Marine Growth Prevention Systems (MGPS) effective for vessel biosecurity? - Bailey Lovett; Patrick Cahill; Javier Atalah; Julien Vignier; Lauren Fletcher; Juliette Butler; Hannah Appleton; Olivier Champeau; Matthew Reardon; Eugene Georgiades; Yasmin Gabay; Daniel Kluza; et al. (Marine Pollution Bulletin, 2025)

How Do Synchrony in Survival and Productivity Influence Abundance Synchrony in European Landbirds? - Catriona A. Morrison; Jennifer A. Gill; Claire Buchan; Robert A. Robinson; Juan Arizaga; Oriol Baltà; Emanuel Baltag; Jaroslav Cepák; Pierre‐Yves Henry; Ian Henshaw; Zsolt Karcza; Petteri Lehikoinen; et al. (Ecology Letters, 2025)
Synchronous fluctuations in species' abundance are influenced by synchrony in underlying rates of productivity and survival. However, it remains unclear how rate synchrony varies in space and time, contributes to abundance synchrony, and differs among species. Using long‐term annual count (number of adults captured), adult survival and productivity (number of juveniles captured per adult) data for breeding land‐birds at ringing sites across Europe, we show that synchrony is strongest and largest scale in productivity and weakest and smallest scale in counts. However, counts fluctuate more synchronously with survival than they do with productivity. These patterns hold for species which do not migrate or only migrate within Europe (European‐residents) and those migrating to sub‐Saharan Africa (subSaharan‐migrants), but the periodicity of productivity and survival synchrony is longer in European‐residents than in subSaharan‐migrants. This suggests that survival and productivity synchrony may interact to weaken abundance fluctuations but are influenced by environmental drivers operating over differing timescales in European‐resident and subSaharan‐migrant species.

Intercomparison of global foliar trait maps reveals fundamental differences and limitations of upscaling approaches - Benjamin Dechant; Jens Kattge; Ryan Pavlick; Fabian D. Schneider; Francesco M. Sabatini; Álvaro Moreno-Martínez; Ethan E. Butler; Peter M. van Bodegom; Helena Vallicrosa; Teja Kattenborn; Coline C.F. Boonman; Nima Madani; et al. (Remote Sensing of Environment, 2024)

X-ray translucent reaction cell for simulation of carbon mineral storage reservoir environments - Ian D. Watt; Ian B. Butler; James Gilgannon; Lucas Martins; Florian Fusseis; R. Stuart Haszeldine; Ian Molnar; Stuart M.V. Gilfillan (International Journal of Greenhouse Gas Control, 2024)

Control of brine composition over reactive transport processes in calcium carbonate rock dissolution: Time-lapse imaging of evolving dissolution patterns - Priyanka Agrawal; Hamed Aslannejad; Arjen Mascini; Tom Bultreys; Amir Raoof; Veerle Cnudde; Ian B. Butler; Mariëtte Wolthers (Applied Geochemistry, 2024)

Pectin as a biopolymer source for packaging films using a circular economy approach: Origins, extraction, structure and films properties - Ian P. Butler; Russell A. Banta; Andrey A. Tyuftin; Justin Holmes; Shivani Pathania; Joe Kerry (Food Packaging and Shelf Life, 2023)

Integrating management of marine activities in Australia - Robert L. Stephenson; Alistair J. Hobday; Ian Butler; Toni Cannard; Mel Cowlishaw; Ian Cresswell; Christopher Cvitanovic; Jon C. Day; Kirstin Dobbs; Leo X.C. Dutra; Stewart Frusher; Maree Fudge; et al. (Ocean & Coastal Management, 2023)

Crystallisation pathways of a mixed La Nd carbonate – Ambient temperature synthesis of the mineral lanthanite - Dylan L. Price; Ian B. Butler; Bryne T. Ngwenya; Linda A. Kirstein; Frank McDermott; Tiina O'Neill (Chemical Geology, 2023)

The functions of repressor element 1-silencing transcription factor in models of epileptogenesis and post-ischemia - Ruth Butler-Ryan; Ian C. Wood (Metabolic Brain Disease, 2021)
Epilepsy is a debilitating neurological disorder characterised by recurrent seizures for which 30% of patients are refractory to current treatments. The genetic and molecular aetiologies behind epilepsy are under investigation with the goal of developing new epilepsy medications. The transcriptional repressor REST (Repressor Element 1-Silencing Transcription factor) is a focus of interest as it is consistently upregulated in epilepsy patients and following brain insult in animal models of epilepsy and ischemia. This review analyses data from different epilepsy models and discusses the contribution of REST to epileptogenesis. We propose that in healthy brains REST acts in a protective manner to homeostatically downregulate increases in excitability, to protect against seizure through downregulation of BDNF (Brain-Derived Neurotrophic Factor) and its receptor, TrkB (Tropomyosin receptor kinase B). However, in epilepsy patients and post-seizure, REST may increase to a larger degree, which allows downregulation of the glutamate receptor subunit GluR2. This leads to AMPA glutamate receptors lacking GluR2 subunits, which have increased permeability to Ca 2+ , causing excitotoxicity, cell death and seizure. This concept highlights therapeutic potential of REST modulation through gene therapy in epilepsy patients.

Sarcopenia during COVID-19 lockdown restrictions: long-term health effects of short-term muscle loss - Richard Kirwan; Deaglan McCullough; Tom Butler; Fatima Perez de Heredia; Ian G. Davies; Claire Stewart (GeroScience, 2020)
The COVID-19 pandemic is an extraordinary global emergency that has led to the implementation of unprecedented measures in order to stem the spread of the infection. Internationally, governments are enforcing measures such as travel bans, quarantine, isolation, and social distancing leading to an extended period of time at home. This has resulted in reductions in physical activity and changes in dietary intakes that have the potential to accelerate sarcopenia, a deterioration of muscle mass and function (more likely in older populations), as well as increases in body fat. These changes in body composition are associated with a number of chronic, lifestyle diseases including cardiovascular disease (CVD), diabetes, osteoporosis, frailty, cognitive decline, and depression. Furthermore, CVD, diabetes, and elevated body fat are associated with greater risk of COVID-19 infection and more severe symptomology, underscoring the importance of avoiding the development of such morbidities. Here we review mechanisms of sarcopenia and their relation to the current data on the effects of COVID-19 confinement on physical activity, dietary habits, sleep, and stress as well as extended bed rest due to COVID-19 hospitalization. The potential of these factors to lead to an increased likelihood of muscle loss and chronic disease will be discussed. By offering a number of home-based strategies including resistance exercise, higher protein intakes and supplementation, we can potentially guide public health authorities to avoid a lifestyle disease and rehabilitation crisis post-COVID-19. Such strategies may also serve as useful preventative measures for reducing the likelihood of sarcopenia in general and in the event of future periods of isolation.

Combined visual and biochemical analyses confirm depositor and diet for Neolithic coprolites from Skara Brae - Andrzej A. Romaniuk; Elsa Panciroli; Michael Buckley; Manasij Pal Chowdhury; Carla Willars; Jeremy S. Herman; Lore G. Troalen; Alexandra N. Shepherd; David V. Clarke; Alison Sheridan; Bart E. van Dongen; Ian B. Butler; et al. (Archaeological and Anthropological Sciences, 2020)
Coprolites (fossilized faeces) can provide valuable insights into species’ diet and related habits. In archaeozoological contexts, they are a potential source of information on human-animal interactions as well as human and animal subsistence. However, despite a broad discussion on coprolites in archaeology, such finds are rarely subject to detailed examination by researchers, perhaps due to the destructive nature of traditional analytical methods. Here, we have examined coprolitic remains from the Neolithic (third millennium BCE) settlement at Skara Brae, Orkney, using a range of modern methods: X-ray computed tomography, scanning electron microscopy, lipid and protein analysis (shotgun proteomics of the coprolite matrix as well as collagen peptide mass fingerprinting of isolated bone fragments). This combined approach minimised destructiveness of sampling, leaving sufficient material for subsequent study, while providing more information than traditional morphological examination alone. Based on gross visual examination, coprolites were predominantly attributed to domestic dogs ( Canis familiaris ), with morphologically identified bone inclusions derived from domestic sheep ( Ovis aries ) and common voles ( Microtus arvalis ). Partial dissection of a coprolite provided bone samples containing protein markers akin to those of domestic sheep. Considering the predominance of vertebral and distal limb bone fragments, Skara Brae dogs were probably consuming human butchery or meal refuse, either routinely fed to them or scavenged. The presumably opportunistic consumption of rodents may also have played a role in pest control.

Understanding the effects of recreational catch‐and‐release angling on an increasingly important foreign fishing tourism species, the giant African threadfin Polydactylus quadrifilis (Cuvier) - Edward Claude Butler; Amber‐Robyn Childs; Murray Ian Duncan; Warren Mason Potts (Fisheries Management and Ecology, 2020)
Foreign fishing tourism (FFT) is becoming increasingly popular in the developing world, where it often coexists alongside other important sectors involving domestic recreational anglers and dependant artisanal and subsistence fishing communities. Therefore, it is important that FFT operations use effective catch‐and‐release (C&R) angling to minimise negative impacts to locally important fishery species. Using reflex action mortality predictors (RAMPs) and physiological stress indicators, this study assessed the impacts of C&R angling within the FFT fishery targeting Polydactylus quadrifilis (Cuvier) on the Kwanza Estuary, Angola. Air exposure (cumulative link model (CLM): Z = 3.99, p p = 0.02) significantly predicted increased motor impairment. Handling practices were particularly important for larger reproductively valuable individuals as fish size was positively correlated with fight (Spearman's rank: r = 0.85, p r = 0.70, p

Contrasting Futures for Australia’s Fisheries Stocks Under IPCC RCP8.5 Emissions – A Multi-Ecosystem Model Approach - Heidi R. Pethybridge; Elizabeth A. Fulton; Alistair J. Hobday; Julia Blanchard; Catherine M. Bulman; Ian R. Butler; William W. L. Cheung; Leo X. C. Dutra; Rebecca Gorton; Trevor Hutton; Richard Matear; Hector Lozano-Montes; et al. (Frontiers in Marine Science, 2020)

Mesolithic human occupation and seasonality: sclerochronology, δ18O isotope geochemistry, and diagenesis verification by Raman and LA-ICP-MS analysis of Argyrosomus regius (meagre) sagittae otoliths from layer 1 of Cabeço da Amoreira Mesolithic shell midden (Muge, Portugal) - Rita Dias; Juan Estrella-Martínez; Paul Butler; Alexandra Nederbragt; Ian R. Hall; Pedro Barrulas; Anne France Maurer; Ana Mafalda Cardeira; José Mirão; Cleia Detry; Nuno Bicho (Archaeological and Anthropological Sciences, 2019)

Molecular and morphological insights into the origin of the invasive greater white-toothed shrew (Crocidura russula) in Ireland - Laura M. Gargan; Raphaël Cornette; Jon M. Yearsley; W. Ian Montgomery; Joana Paupério; Paulo C. Alves; Fidelma Butler; Michel Pascal; Anne Tresset; Anthony Herrel; John Lusby; David G. Tosh; et al. (Biological Invasions, 2016)

Mobilization of horizontally acquired island 2 is induced in planta in the phytopathogen P ectobacterium atrosepticum SCRI 1043 and involves the putative relaxase ECA 0613 and quorum sensing - Bhanupratap R. Vanga; Pavithra Ramakrishnan; Ruth C. Butler; Ian K. Toth; Clive W. Ronson; Jeanne M. E. Jacobs; Andrew R. Pitman (Environmental Microbiology, 2015)
Summary Integrative and conjugative elements ( ICEs ) contribute to the rapid evolution of bacterial pathogens via horizontal gene transfer of virulence determinants. ICEs have common mechanisms for transmission, yet the cues triggering this process under natural environmental or physiological conditions are largely unknown. In this study, mobilization of the putative ICE horizontally acquired island 2 ( HAI 2), present in the chromosome of the phytopathogen P ectobacterium atrosepticum SCRI 1043, was examined during infection of the host plant potato. Under these conditions, mobilization of HAI 2 increased markedly compared with in vitro cultures. In planta ‐induced mobilization of HAI 2 was regulated by quorum sensing and involved the putative ICE ‐encoded relaxase ECA 0613. Disruption of ECA 0613 also reduced transcription of genes involved in production of coronafacic acid (Cfa), the major virulence factor harboured on HAI 2, whereas their expression was unaffected in the quorum‐sensing ( expI ) mutant. Thus, suppression of cfa gene expression was not regulated by the mobilization of the ICE per se , but was due directly to inactivation of the relaxase. The identification of genetic factors associated solely with in planta mobilization of an ICE demonstrates that this process is highly adapted to the natural environment of the bacterial host and can influence the expression of virulence determinants.

Consulting Forestry / Certification and Ecosystem Services - James Coufal; Carl Wiedemann; Jacob Gorman; Larry Teeter; Yaoqi Zhang; Michael Kilgore; Kristell Miller; Stephanie Snyder; Sun Chang; Miriam Davis; Stanley Asah; J. Mark Fly; et al. (Journal of Forestry, 2011)
45The industrialization of the United States throughout the 19th century resulted in the exploitation of millions of acres of timberland across the country. Logging during that era was described by critics as “cut out and get out” because the land was usually abandoned after the merchantable timber was exhausted. Concern about future timber supplies and the effect of logging on watersheds spurred the development of professional forestry after the Civil War. The first forestry leaders, including Bernhard Fernow and Gifford Pinchot, encouraged private non-industrial forest owners to sustainably manage their woodlands and specifically warned against destructive logging practices—including “cutting the best and leaving the rest”—aka high-grading. During the 1920s and 30s both the Forest Service and SAF spurred initiatives to encourage sustainable timber harvesting practices on private forestland. Although great progress has been made in forest management, logging on most private non-industrial forest land in the east has not changed significantly since the 19th century. Landowners usually sell timber without using the services of a forester, allowing the buyer to selectively cut the most valuable trees in the woodlot. Although this can reduce future value by 70-90%, it remains common practice because both the landowner and the timber buyer maximize short term income. The timber value and productivity of millions of acres of woodland throughout the United States have been significantly degraded as a result. This paper will trace the history of high-grading as described by forestry leaders from the 19th century through the 21st and will show that much work remains unfinished.

Forest Policy / Biosecurity - Linda Heath; Clark Row; Robert Perschel; Douglas Boucher; Patricia Elias; Katherine Lininger; Calen May-Tobin; Earl Saxon; Steven Ruddell; Sally Collins; Sarah Ruddell; Mo Zhou; et al. (Journal of Forestry, 2011)
7Massive fires in Indonesian peatlands in the 1990s and in eastern Russian peatlands in 2002 and last year have highlighted the need to manage forests overlying peat deposits, as well as converted peat forests and open peatlands. Peat or peaty soils, contain 65% or more of partially decayed vegetation, can burn freely or underground. They cover some 10 percent of worldwide forests and contain 25 percent of all terrestrial carbon. Recent massive greenhouse gas (GHG) emissions from fires in forested peat and peatland in Indonesia and in Russia highlight the need for policies to reduce GHG emissions. We discuss major peatland areas and quantify their carbon stocks and potential GHG emissions. Trends show that year-to-year emissions are variable, with huge pulses that are a significant share of global GHG emissions. We group suggested policy options into three approaches. The first approach, which will reduce peat-related product demand, includes a) restricting peat, and products produced on cleared forested peatland, from being labeled or counted in GHG reduction achievements, as renewable (which palm oil currently is considered); b) developing full substitutes for horticultural peat (comprising about half mined peat use); and c) developing renewable power in countries still dependent on peat for power generation. These options reduce the rate of developing newly mined peat/forest areas. Options for a second approach, which treat already drained and cleared forested peatlands, are: d) restoring functioning peat ecosystems by closing drainage ditches, allowing natural rewetting, and “seeding” with peat vegetation fragments, e) requiring current peat operators to restore mined areas right after all peat is removed, and f) converting them to other land uses, despite the acidic conditions of mined peat bogs. These options sharply reduce risks of peat fires. Finally, a third group of policy options reduces ignition risks and limit fire spread: g) developing monitoring, suppression techniques, h) organizing local landowner protection groups and i) improving public fire organizations.

Auditory facilitation of visual-target detection persists regardless of retinal eccentricity and despite wide audiovisual misalignments - Ian C. Fiebelkorn; John J. Foxe; John S. Butler; Sophie Molholm (Experimental Brain Research, 2011)

Tracking macaroni penguins during long foraging trips using ‘behavioural geolocation’ - Jonathan A. Green; Rory P. Wilson; Ian L. Boyd; Anthony J. Woakes; Chris J. Green; Patrick J. Butler (Polar Biology, 2009)

Mammalian browsing impact on regenerating Eucalyptus seedlings in a large commercially managed native forest estate - Julian Di Stefano; Kym Butler; Ian Sebire; Peter Fagg (New Forests, 2009)

Applications of pedigree-based genome mapping in wheat and barley breeding programs - Mandy Christopher; Emma Mace; David Jordan; David Rodgers; Paul McGowan; Ian Delacy; Phillip Banks; John Sheppard; David Butler; David Poulsen (Euphytica, 2007)

Genetic mapping of a major gene affecting onion bulb fructan content - John McCallum; Andrew Clarke; Meeghan Pither-Joyce; Martin Shaw; Ruth Butler; Don Brash; John Scheffer; Ian Sims; Sjaak van Heusden; Masayoshi Shigyo; Michael J. Havey (Theoretical and Applied Genetics, 2006)

On the mechanism of action of thiamin enzymes, Crystal structure of 2-(α-hydroxyethyl)thiamin pyrophosphate (HETPP). Complexes of HETPP with zinc(II) and cadmium(II) - Gerasimos Malandrinos; Maria Louloudi; Cristiana A. Mitsopoulou; Ian S. Butler; Robert Bau; N. Hadjiliadis (JBIC Journal of Biological Inorganic Chemistry, 1998)